The concept of integrity for Muslim's character based on Al-Ghazali's ethical perspective - Shuhari, Mohd Hasrul; Hamat, Mohd Fauzi; al-Shafi'i, Mohammed Muneer'deen Olodo; Wan Jusoh, Wan Hishamudin; Mohamad Zin, Siti Aisyah; Wahab, Muhammad Rashidi (Allied Business Academies, 2019)
Integrity is one of the moral qualities of human that needs to be translated into everyday life particularly by Muslim individuals. It also refers to ethic, a principle that is followed daily. A person's character consists of the combination of qualities that make up his personality, and it is this attribute that motivates a person to avoid something that could cause him to be considered an individual without integrity. The characteristics of a person without integrity include deception, treachery, deviance, corruption, money politics and the likes. These characteristics could be avoided if one adorns oneself with elements of integrity such al-Sidq (truthfulness). Al-Sidq is elaborated based on the thought of al-Ghazali in his Ihya' 'Ulum al-Din. This article concludes that al-Sidq refers to six definitions which include the word, intent and will, determination and its fulfillment, balance and preference between spiritual and physical practices, and religious maqam (status). It establishes the quality of integrity within Muslim individuals. © 2019, Allied Business Academies.